PARENT – ASSESSMENT OF PARENTAL ATTITUDES REGARDING EXERCISE AND NEUROMUSCULAR THERAPY IN ROMANIA - Cherecheș Ștefania; Bulduș Codruța Florina (Sport şi Societate)
Recognizing the vital role of parental satisfaction in Pediatric Physical Therapy, our study aims to improve service quality provided by physiotherapists in Romania. The absence of standardized tools to assess these services complicates evaluation efforts. Given that parental involvement is key to the success and continuity of children's therapies, understanding their perspectives becomes crucial for measuring the quality and efficacy of physical therapy services.Our research examines the current state of Pediatric Physical Therapy in Romania, focusing on parental attitudes toward the services their children have received. This study seeks to offer initial guidance for developing standardized tools to enhance service quality.Taking an innovative approach, we adapted the MedRisk Instrument for Evaluating Patient Satisfaction with Physical Therapy Care (MRPS) to fit the Romanian healthcare context. This process involved translating and back-translating the 13-item MRPS into Romanian, customizing it for cultural relevance, and ensuring clarity for caregivers. We created a Romanian version of the tool that caregivers could easily understand and complete. To collect data, we distributed our internet-based questionnaire to a diverse group of individuals.Starting March 2nd, 2024, we conducted a survey with 39 parents who volunteered to share theirinitial experiences with the therapeutic process and factors influencing their satisfaction and likelihood of returning to the clinic. These insights are crucial for assessing the tool's accuracy and consistency. The modifications to the MedRisk tool and primary findings contribute to research on parental satisfaction in Pediatric Physical Therapy in Romania, suggesting the tool's potential effectiveness for future studies.